Analysis of the Minha Casa MInha Vida Program, and the next steps to reduce the housing deficit according to the literature (Research, Society and Development, 2023)
The Minha Casa Minha Vida (MCMV) program was created in 2009 and its status was boosted after Brazil's housing policy, and since then there is a gap in the development of other housing supply alternatives. This study presents a diagnosis of recent housing policies in Brazil, particularly of the different ways in which the MCMV operates, pointing out some criticisms, such as the low spatial adherence between deficits and housing production and attendance to the four components typically considered unequal. Deficit calculations, housing, etc. As a way to overcome these challenges, this article details two options that can be combined or expanded independently to increase social access to basic housing rights: Social Housing Production (PSM) and Social Housing Leasing Services (SLS).